2021
DOI: 10.1088/1742-6596/1943/1/012072
|View full text |Cite
|
Sign up to set email alerts
|

Potential of water hyacinth (Eichhornia crassipes (Mart.) Solms) in Rawapening lake as raw material for fish feed

Abstract: Feed is a major factor in determining the success of aquaculture business. The quality and quantity of feeding properly will maximize the growth of fish. Various research and application of technology has been made to obtain alternative feed source so as to reduce the level of dependence on the food production industry. The eutrophication condition of Rawapening Lake has triggered the water hyacinth (Eichhornia crassipes (Mart.) Solms) to grow out of control. It speeds up the loss of water weeds, cover the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…On the other hand, water hyacinth has the potential to be used as phytoremediation, paper, organic fertilizer, biogas production, human food, fiber, livestock feed, as an ornamental plant and even its biomass has the potential to be a source of renewable energy (Jafari, 2010;Rezania et al, 2015). The same thing happened to Rawa Pening Lake with the hyacinth growth rate ranging from 6.40-7.26%/day (Prasetyo et al, 2022), which can trigger the lake siltation because the root system of hyacinth allows high sediment trapping. The measurements of sedimentation and water quality of Rawa Pening Lake conducted in 2015 revealed that the lake underwent shrinking and siltation which resulted in the effective area of the lake becoming 1,850 ha with a reservoir volume of 48.15 million m3 (elevation +463).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, water hyacinth has the potential to be used as phytoremediation, paper, organic fertilizer, biogas production, human food, fiber, livestock feed, as an ornamental plant and even its biomass has the potential to be a source of renewable energy (Jafari, 2010;Rezania et al, 2015). The same thing happened to Rawa Pening Lake with the hyacinth growth rate ranging from 6.40-7.26%/day (Prasetyo et al, 2022), which can trigger the lake siltation because the root system of hyacinth allows high sediment trapping. The measurements of sedimentation and water quality of Rawa Pening Lake conducted in 2015 revealed that the lake underwent shrinking and siltation which resulted in the effective area of the lake becoming 1,850 ha with a reservoir volume of 48.15 million m3 (elevation +463).…”
Section: Resultsmentioning
confidence: 99%
“…Water hyacinth (Eichornia crassipes) is an aquatic weed that has a high growth rate so it can damage the aquatic environment (Kurniadie et al, 2023;Prasetyo et al, 2022), including increasing evapotranspiration (evaporation and loss of water through the leaves within 52 days, each water hyacinth stem is capable of producing 1 m 2 of new plants. The use of water hyacinth plants as fertilizer because the remaining organic matter Sofyan et al (2023), from these plants contains a lot of macro nutrients such as N, P, K which are needed for the growth of cultivated plants (Peng et al, 2023).…”
Section: Introductionmentioning
confidence: 99%